Evaluation of the nutrient inputs to a coastal lagoon: the case of the Ria de Aveiro, Portugal - Silva, J. Figueiredo da (2002)
The Ria de Aveiro estuary-coastal lagoon system of northern Portugal is estimated to currently receive mean annual influxes of total nitrogen (N) and total phosphorus (P) of c. 6118 t y−1 and 779 t y−1, respectively, from its influent rivers. In low summer flows the mean N and P fluxes decrease to c. 10% of the annual average. The sewage contribution to the inland-derived N load on an annual basis is c. 5% but, during the summer low flow conditions, the sewage component increases to c. 65% of the total river loading. The sewage contribution to the inland-derived P load on an annual basis is c. 11% but, during the dry season, it is 1.2 times larger than the river-derived flux. The construction of a regional sewer system linked to a submarine outfall, due for completion in 2005, is expected to lead to a reduction in nutrient fluxes from inland to the lagoon of c. 15% for N and c. 26% for P relative to the present values. While this system will reduce the nutrient loading in the upper reaches of the lagoon, an increase in nutrients derived from the ocean is anticipated, due to the proximity of the outfall to the inlet.